Electro-coagulation coupled with solid carrier enhanced GDCMBR as pretreatment for NF dual membrane system during surface brackish water treatment. (20th December 2022) - Wang, Qiao; Xiao, Mengyao; Rao, Peng; Zhao, Wentao; Wang, Zhihong; Du, Xing; Tian, Jiayu
Abstract: The novel electrocoagulation (EC) coupled with solid carriers enhanced gravity-driven ceramic membrane bioreactor (GDCMBR) as pretreatment for nanofiltration (NF) dual membrane system was conducted to surface brackish water treatment for long-term (85 days) operation, at a current density of 2 mA/cm 2 and hydraulic retention time of 9 min, 172 min for EC cell, GDCMBR with solid carriers respectively. Warm operation condition was beneficial to improve permeate flux, and it can reach up to 33.0 L/m 2 /h at ∼25 °C. In particular, the addition of solid carriers endowed the EC-GDCMBR system with a higher stable flux, due to the mitigation of fouling layer. The biofilms on the filler and membrane enabled to completely remove NH3 –N via biological nitrification and denitrification, verifying by the progressive growth of Nitrospira, Bacteroide and Helicobacter in high-throughput sequencing. In EC-GDCMBR pretreatment, the organic substances and particulate matters could be effectively eliminated. Owing to the hypersaline property of surface brackish water, the electric flocculation effect was obviously enhanced, especially for UV254 removal. Moreover, the subsequent NF unit played a major role in dislodging the hardness and salinity from the final effluent. In addition, EC-GDCMBR-NF dual membrane system also enabled to remove micropollutants (i.e. antibiotics), in which the purification mechanism could be ascribed to the biofilm adsorption and NF membrane rejection. Overall, the results of this study suggest the potential for long-term operation during brackish water purification. Graphical abstract: Image 1 Highlights: The addition of solid carriers endowed the EC-GDCMBR system to obtain a higher stable flux. The increased operating temperature was beneficial to flux improvement and biofilm growth of GDCMBR. The loaded on the carriers and enriched on biofilm enabled to completely remove NH3 –N via biological nitrification. The EC-GDCMBR-NF dual membrane system also enabled to dislodge the micropollutants.